Poll- otter architecture : For an urban environment sinking under layers of barriers : With focus on the boundary wall as an architectural medium to support the urban condition - Pienaar, Marguerite (University of Pretoria, 2018)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2018.